”Kasama Weki” in the Architecture of the West Nusa Tenggara Weaving Museum - Nafasia, Sahadat; Anggita, Diptya (Journal of Aesthetics, Creativity and Art Management, 2024)
The aim of this research is to incorporate the wisdom of West Nusa Tenggara, Indonesia, into the design of the museum building, to preserve culture as a symbol of respect and love for the Indonesian homeland. The approach is carried out using a qualitative-correlational analysis approach to local socio-cultural activities and also using a conceptual design approach regarding design themes that highlight a cultural wisdom in Dompu called "Kasama Weki". "Kasama Weki" is the advice of Bima-Dompu West Nusa Tenggara which means togetherness, solidarity, kinship, justice, volunteerism (selfless), responsibility, active role of society as well as unity and oneness. This advice has locality and synergy values contained in the Bima-Dompu culture so that it can be applied in the design of the weaving museum building. "Kasama Weki" as an international tourist attraction is based on a series of cultural thematics as part of the design concept. The application of this theme is a symbol of respect and love for Indonesia's homeland so that it becomes an iconic architectural work as a contextual and communicative platform and as an educational tourist attraction and has the potential on the international stage to advance tourism and the creative economy which spurs improvements in the quality of Indonesian woven products in accordance with the spirit of Sustainable Development Goals (SDGs).